Prevalence of self-medication in the adult population of Brazil: a systematic review - Domingues,Paulo Henrique Faria (2015)
OBJECTIVE To evaluate the prevalence of self-medication in Brazil’s adult population.METHODS Systematic review of cross-sectional population-based studies. The following databases were used: Medline, Embase, Scopus, ISI, CINAHL, Cochrane Library, CRD, Lilacs, SciELO, the Banco de teses brasileiras(Brazilian theses database) (Capes) and files from the Portal Domínio Público (Brazilian Public Domain). In addition, the reference lists from relevant studies were examined to identify potentially eligible articles. There were no applied restrictions in terms of the publication date, language or publication status. Data related to publication, population, methods and prevalence of self-medication were extracted by three independent researchers. Methodological quality was assessed following eight criteria related to sampling, measurement and presentation of results. The prevalences were measured from participants who used at least one medication during the recall period of the studies.RESULTS The literature screening identified 2,778 records, from which 12 were included for analysis. Most studies were conducted in the Southeastern region of Brazil, after 2000 and with a 15-day recall period. Only five studies achieved high methodological quality, of which one study had a 7-day recall period, in which the prevalence of self-medication was 22.9% (95%CI 14.6;33.9). The prevalence of self-medication in three studies of high methodological quality with a 15-day recall period was 35.0% (95%CI 29.0;40.0, I2 = 83.9%) in the adult Brazilian population.CONCLUSIONS Despite differences in the methodologies of the included studies, the results of this systematic review indicate that a significant proportion of the adult Brazilian population self-medicates. It is suggested that future research projects that assess self-medication in Brazil standardize their methods.